Mannose-binding lectin gene sequence data in Kelantan population - Muhamad Aidil Zahidin; Noor Haslina Mohd Noor; Muhammad Farid Johan; Abu Dzarr Abdullah; Zefarina Zulkafli; Hisham Atan Edinur (Scientific Data)
Abstract The human mannose-binding lectin (MBL) gene encodes a polymorphic protein that plays a crucial role in the innate immune response. Human MBL deficiency is associated with immunodeficiencies, and its variants have been linked to autoimmune and infectious diseases. Despite this significance, gene studies concerning MBL sequencing are uncommon in Malaysia. Therefore, we aimed to preliminary described the human MBL sequencing dataset based on the Kelantan population. Blood samples were collected from 30 unrelated individuals and underwent DNA extraction, genotyping, and sequencing. The sequencing data generated 886 bp, which were deposited in GenBank (ON619541-ON619546). Allelic variants were identified and translated into six MBL haplotypes: HYPA, HYPB, LYPB, LXPB, HXPA, and LXPA. An evolutionary tree was constructed using the haplotype sequences. These findings contribute to the expansion of MBL information within the country, providing a valuable baseline for future research exploring the association between the gene and targeted diseases.